Chronic Venous Insuffi ciency in a Woman with Standing Profession - Mustika Mahbubi; Muhamad Taufik Ismail; Erika Maharani; Hariadi Hariawan (ACI (Acta Cardiologia Indonesiana), 2016)
The prevalence of Chronic Venous Insufficiency (CVI) give a high social impact. InEurope, approximately 40% of the adult population affected by venous disorders. In general, the prevalence of CVI is about 5% - 15%. The prevalence is increasing by age.